2016
DOI: 10.5897/jphe2015.0752
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices of health care workers on Ebola virus disease in Conakry, Guinea: A cross-sectional study

Abstract: In the current Ebola virus disease (EVD) outbreak, health care workers (HCWs) are on the frontline of the response. The study aimed to report on the knowledge, attitudes and practices of Conakry HCWs. A cross-sectional survey was done among HCWs from the two national hospitals and at the communal hospitals in Conakry, using a standardized questionnaire. Demographic, knowledge, attitudes and practices data of the respondents were recorded and analyzed. Respondents (n = 525) were mainly physicians (43.0%) or nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In this survey, householder and driver occupation were associated with a negative attitude. During the Ebola outbreak in DRC and Guinea, it was found that a group of participants had a negative attitude toward measures for prevention of Ebola in their respective areas (15,24) the same as for a study done among Chinese residents during the coronavirus pandemic (6). Among confirmed cases in Uganda, one-third are truck drivers who are coming from surrounding countries (10).…”
Section: Discussionmentioning
confidence: 95%
“…In this survey, householder and driver occupation were associated with a negative attitude. During the Ebola outbreak in DRC and Guinea, it was found that a group of participants had a negative attitude toward measures for prevention of Ebola in their respective areas (15,24) the same as for a study done among Chinese residents during the coronavirus pandemic (6). Among confirmed cases in Uganda, one-third are truck drivers who are coming from surrounding countries (10).…”
Section: Discussionmentioning
confidence: 95%
“…Most Ebola cases in Guinea resulted from the washing and touching of persons and corpses infected with Ebola without adequate infection control precautions at home, at funerals, and in health facilities ( 2 , 3 ). As the 18-month epidemic waned in August 2015, Ebola KAP were assessed in a survey among residents of Guinea recruited through multistage cluster sampling procedures in the nation’s eight administrative regions (Boké, Conakry, Faranah, Kankan, Kindia, Labé, Mamou, and Nzérékoré).…”
mentioning
confidence: 99%
“…Referring to Chou and Hu (2015), subjective evaluation is applied to measure sleep quality with sleeping time and quality level. Davey et al (2015) mentioned that, with the rapidly increasing new knowledge in basic medicine science, preventive medicine, and clinical medicine as well as the rapid advance of medical technology development, continuing medical education could ensure physicians presenting adequate professional abilities and being competent of medical businesses in the future career to reduce physicians' job stress and enhance the healthcare quality (Touré et al, 2016). Pritchard (2017) explained that continuing medical education as the education or training to enhance or develop professional medical knowledge, the abilities of inference and explanation, and appropriate professional skills to complete the doctor-patient relationship standard or ability and effectively reduce medical staff's job stress (Hatherill et al, 2016).…”
Section: Sleep Qualitymentioning
confidence: 99%
“…When an individual could not acquire the balance with the job, job stress was resulted from individual physical and mental unbalance because of work requirements or the expectation of self-actualization in the work environment (Nyberget al, 2013). Heinen et al (2013) defined job stress as the response harmful for body or emotion when the work requirement could not conform to the worker's capability, resources, or personal needs; job stress would result in bad health and even cause damage (Touré et al, 2016). Johns and Jepsen (2015) proposed experts' definition of job stress as the job requirements not being able to conform to the worker's responsibility, resources, or job needs.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%